THE USE OF PODCAST TO IMPROVE STUDENTS’ LISTENING COMPREHENSION - Hania Fadhilatun Nisa; Lidyatul Izzah; Muhamad Sofian Hadi (STKIP Siliwangi, 2022)
This study aims to investigate the effectiveness of podcast in improving students’ listening skill. The method used in this research is quantitative method with pre-experimental as a research design. Both the pre-test and post-test were used as instruments in collecting data. The writer used one class in the seventh grade of SMP Muhammadiyah 35 Jakarta as the sample. The data were analyzed statistically using t-test. The results of the analysis show that the mean score of students is 89.4, statistical calculations show the result to (t-observation) > t (t-table) obtained are 17.986 while the Tt value is 1.721 with a significant level of 5% (0.05), because To is higher than Tt, then the alternative hypothesis (Ha) was accepted while the null hypothesis was rejected. From the result of this analysis this study concludes that using Podcast was an effective media to improve students’ listening skills.